Nutrition in the paediatric surgical patient. Issue 5 (May 2016) - Eaton, Simon; Carnaghan, Helen
Abstract: Nutritional care of surgical infants and children is of major importance. This is for several reasons: (i) body stores are often smaller and more precarious; (ii) infants and children not only require energy for maintenance, but also for growth; and (iii) as in adults, recovery from surgery is faster in those patients who are adequately nourished. Survival of infants with congenital anomalies dramatically improved following the introduction of parenteral nutrition. However, infection and cholestasis remain problematic for parenterally fed infants and children.